BK Virus Load Associated with Serum Levels of sCD30 in Renal Transplant Recipients - Haidar A. Shamran; Salma N. Malik; Jinan M. Al-Saffer; Rana S. Jawad (International Journal of Microbiology)
Background. Rejection is the main drawback facing the renal transplant operations. Complicated and overlapping factors, mainly related to the immune system, are responsible for this rejection. Elevated serum levels of sCD30 were frequently recorded as an indicator for renal allograft rejection, while BV virus is considered as one of the most serious consequences for immunosuppressive treatment of renal transplant recipients (RTRs). Aims. This study aimed to determine the association of BK virus load with serum levels of sCD30 in RTRs suffering from nephropathy. Patients and Methods. A total of 50 RTRs with nephropathy and 30 age-matched apparently healthy individuals were recruited for this study. Serum samples were obtained from each participant. Real-time PCR was used to quantify BK virus load in RTRs serum, while ELISA technique was employed to estimate serum levels of sCD30. Results. Twenty-two percent of RTRs had detectable BKV with mean viral load of 1.094E + 06 ± 2.291E + 06. RTRs showed higher mean serum level of sCD30 (20.669±18.713 U/mL) than that of controls (5.517±5.304 U/mL) with significant difference. BK virus load had significant positive correlation with the serum levels of sCD30 in RTRs group. Conclusion. These results suggest that serum levels of sCD30 could be used as an indicator of BK viremia, and accordingly the immunosuppressive regime should be adjusted.